Implementation of a comprehensive safer conception intervention for HIV‐serodiscordant couples in Kenya: uptake, use and effectiveness. Issue 4 (7th April 2019) - Heffron, Renee; Ngure, Kenneth; Velloza, Jennifer; Kiptinness, Catherine; Quame‐Amalgo, Justice; Oluch, Lynda; Thuo, Nicholas; Njoroge, John; Momanyi, Richard; Gakuo, Stephen; Mbugua, Sarah; Morrison, Susan; et al.
Abstract: Introduction: Safer conception strategies minimize HIV risk during condomless sex to become pregnant. Gaps remain in understanding the acceptability, feasibility and choices HIV‐serodiscordant couples make when multiple safer conception options are available. Methods: We conducted a pilot study of a comprehensive safer conception package for HIV‐serodiscordant couples with immediate fertility desires in Kenya from March 2016 to April 2018. The intervention package included antiretroviral therapy (ART) for HIV‐positive partners, oral pre‐exposure prophylaxis (PrEP) for HIV‐negative partners, daily fertility and sexual behaviour tracking via short message service (SMS) surveys, counselling on self‐insemination, and referrals for voluntary medical male circumcision and fertility care. Couples attended monthly visits until pregnancy with HIV testing for negative partners at each visit. We estimated the number of expected HIV seroconversions using a counterfactual cohort simulated from gender‐matched couples in the placebo arm of a previous PrEP clinical trial. We used bootstrap methods to compare expected and observed seroconversions. Results: Of the 74 enrolled couples, 54% were HIV‐negative female/HIV‐positive male couples. The 6 and 12‐month cumulative pregnancy rates were 45.3% and 61.9% respectively. In the month preceding pregnancy, 80.9% of HIV‐positive partners were virally suppressed, 81.4% of HIV‐negative partners were highly adherent to PrEP, and SMS surveys indicated potential timing of condomless sex to peak fertility (median of sex acts = 10, interquartile range (IQR) 7 to 12; median condomless sex acts = 3.5, IQR 1 to 7). Most (95.7%) pregnancies were protected by ≥2 strategies: 57.4% were protected by high PrEP and ART adherence, male circumcision with or without timed condomless sex; 10 (21.3%) were protected by viral suppression in the HIV‐positive partner and male circumcision with or without timed condomless sex; 8 (17.0%) were protected by high PrEP adherence and male circumcision with or without timed condomless sex. We observed 0 HIV seroconversions (95% CI 0.0 to 6.0 per 100 person years), indicating a 100% reduction in HIV risk ( p = 0.04). Conclusions: The use of multiple safer conception strategies, primarily PrEP, ART, male circumcision and/or tracking fertility, was acceptable and feasible for African HIV‐serodiscordant couples and significantly reduced HIV transmission risk. It is important to increase the availability of and counselling about safer conception services in regions with HIV epidemics involving heterosexual transmission and high fertility.